The relationship between sexual health literacy and sexual health attitudes in young adults (Annals of Medical Research, 2025)
Aim: This paper investigated the relationship between sexual health literacy (SHL) of young adults and attitudes toward sexual health.Materials and Methods: This study was descriptive and correlational in design. The sample size included 281 young adults. Data were collected using a personal information form, the Sexual Health Literacy Scale (SHLS), and the Sexual Health Attitude Scale (SHAS). The data were analyzed using the independent-samples t-test, one-way analysis of variance (ANOVA), Welch ANOVA test, Pearson's correlation coefficients, and simple linear regression analysis.Results: Participants’ mean SHLS and SHAS scores were 59.60±10.86 and 149.68±12.43, respectively. Both SHLS and SHAS scores were significantly higher among women compared to men, and among those who had received sexual health education compared to those who had not (p
Keywords: Sexual health; Health literacy; Attitude; Knowledge; Young adult